A lyophilized sterically stabilized liposome-containing docetaxel: in vitro and in vivo evaluation. (2nd January 2017) - Chen, Yuchao; Chen, Jing; Cheng, Yi; Luo, Lihua; Zheng, Pinjing; Tong, Yidan; Li, Zhao
Abstract: Objectives : In this study, an improved lyophilized PEGylated liposomal formulation of docetaxel (DOC) has been developed. Methods : PEGylated docetaxel liposome (PL-DOC) was prepared by thin-film evaporation method and lyophilization. The effect of various components of the lipids and their compatibility with DOC on the entrapment efficiency (EE) of liposome was investigated. The lyophilized PL-DOC was characterized by morphology, particle size, zeta potential, EE, release in vitro and stability. Pharmacokinetics and biodistribution in vivo of lyophilized PL-DOC were also investigated. Results : The optimal liposome formulation was egg phosphatidylcholine (EPC):cholesterol (CH):DSPE-PEG2000:DOC = 56:40:4:4 (molar ratio). Sucrose and mannitol were chosen as cryoprotectant in the lyophilization (cryoprotectant-to-lipid (C/L) mass ratio  = 8:1). The size of lyophilized PL-DOC was 152.3 ± 1.0 nm with negative charge and the EE was 89.75 ± 1.79%. Compared with nonlyophilized PL-DOC, the lyophilized PL-DOC was more stable at 4 °C for six months. The lyophilized PL-DOC also showed the good stability after reconstituted by 5% glucose injection. In vitro release study of PL-DOC showed that PL-DOC had a sustained release effect. After i.v . administration at the dose of 10 mg/kg in rats, a significant increase in the AUC0-∞, MRT0-∞ and t 1/2 was observed in PL-DOC group compared with conventional docetaxel liposome (CL-DOC) and DOC injection (DOC-I) group. Biodistribution studies in mice showed that PL-DOC significantly decreased the uptake by the organs of mononuclear phagocytic system (MPS), such as liver and spleen, while prolonging the retention time of DOC in the plasma. Conclusion : Our PEGylated liposome formulation reported in this study could potentially produce viable clinical strategies for improved delivery of DOC for the treatment of human cancer.